2000
DOI: 10.1177/107110070002100410
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Calf Muscle Size and Strength after Achilles Rupture Repair

Abstract: The object was to study the relationships between calf muscle size and strength in 85 patients an average of 3.1 years after repair of achilles tendon rupture. The isokinetic calf muscle strength results were excellent or good for 73% of the patients, whereas calf muscle size was normal in only 30%. The average plantar flexion peak torque per unit muscle cross-sectional area was higher on the injured side than on the uninjured side. The average calf muscle cross-sectional area deficit was 15+/-9% (p<0.001) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 16 publications
5
35
1
Order By: Relevance
“…Furthermore, objective measurement of ankle plantar flexion/ dorsiflexion range of motion, heel height during heel-raise tests, and calf circumference showed smaller values in the injured leg [30]. This study confirms previous reports that muscle atrophy is a common long-term problem following repair of an acute tendon rupture [31,32]. In addition, Rosso et al examined 52 patients at a mean of 91 months follow-up who underwent traditional open repair, percutaneous repair, or nonoperative treatment.…”
Section: Long-term Deficitssupporting
confidence: 72%
“…Furthermore, objective measurement of ankle plantar flexion/ dorsiflexion range of motion, heel height during heel-raise tests, and calf circumference showed smaller values in the injured leg [30]. This study confirms previous reports that muscle atrophy is a common long-term problem following repair of an acute tendon rupture [31,32]. In addition, Rosso et al examined 52 patients at a mean of 91 months follow-up who underwent traditional open repair, percutaneous repair, or nonoperative treatment.…”
Section: Long-term Deficitssupporting
confidence: 72%
“…The results revealed a loss of posterior muscle compartment area of 18 % in the open group, 19 % with Ma-Griffith and 9 % in Kakiuchi repair group, respectively. While Haggmark et al [6] compared 15 non-operatively with 8 surgically treated patients and showed a significant reduction in calf muscle area (no follow-up stated), Leppilahti et al [13] showed calf muscle atrophy of 15 % on the affected leg in the analysis of CSA by means of CT scans (mean 3.1 years follow-up). In our findings, the CSA was higher after more than 7.5 years of follow-up although not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is consensus that open reconstruction is best suitable for athletes [1]. Whichever treatment is chosen, sequelae from surgical site infections, scar adhesions and sural nerve irritation in operative techniques [37], higher re-rupture rates in conservative treatment [10] and deep vein thrombosis, muscle atrophy [6,13,25], days off work and loss of function for all treatments exist [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Moreover, a disparity between recovery of isokinetic calf muscle strength and recovery of calf size has been reported; muscle strength normalized to a greater extent than did calf size, and strength training increased muscle strength more than muscle size. 11 In our study, the circumference of the involved calf was uniformly smaller than that of the uninvolved calf; however, the difference was small, and the mean atrophy of the calf was 0.8 cm. All patients were able to perform a single-limb toe raise, and the athletes returned to preinjury-level sports activities after surgery.…”
Section: Discussionmentioning
confidence: 86%